2008
DOI: 10.1016/j.eplepsyres.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor properties in catastrophic infantile epilepsy

Abstract: Catastrophic epilepsy due to cortical dysplasia is often intractable to anticonvulsant treatment. Many of the medications used unsuccessfully in treating this disorder are thought to exert at least a portion of their action through enhancement of inhibitory GABA A neurotransmission. In the present study, GABA A receptor properties in resected brain tissue from four infants with infantile spasms and intractable epilepsy due to cortical dysplasia were measured to determine if this clinical resistance to pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…A recent electrophysiologic study of GABA A receptor currents in dissociated neurons from children with FCD revealed pharmacologic properties suggestive of lower α 1 subunit expression in cytomegalic neurons in regions of “severe” cortical dysplasia (Palmini FCD types 2A and 2B plus hemimegalencephaly), as compared with nondysplastic epileptogenic cortex and regions of “mild” cortical dysplasia (Andre et al, 2008). In our own pharmacologic study of GABA A receptor properties in four infants younger than 1 year of age with FCD 2A, responses to benzodiazepines and barbiturates were unchanged compared with age‐matched controls (Jansen et al, 2008), consistent with the preserved α 1 and γ 2 subunit expression levels in this group demonstrated in the current study. Some studies have reported a reduction in inhibitory postsynaptic current frequency in dysplastic neurons (Calcagnotto et al, 2005), whereas others have found no change (Cepeda et al, 2003, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…A recent electrophysiologic study of GABA A receptor currents in dissociated neurons from children with FCD revealed pharmacologic properties suggestive of lower α 1 subunit expression in cytomegalic neurons in regions of “severe” cortical dysplasia (Palmini FCD types 2A and 2B plus hemimegalencephaly), as compared with nondysplastic epileptogenic cortex and regions of “mild” cortical dysplasia (Andre et al, 2008). In our own pharmacologic study of GABA A receptor properties in four infants younger than 1 year of age with FCD 2A, responses to benzodiazepines and barbiturates were unchanged compared with age‐matched controls (Jansen et al, 2008), consistent with the preserved α 1 and γ 2 subunit expression levels in this group demonstrated in the current study. Some studies have reported a reduction in inhibitory postsynaptic current frequency in dysplastic neurons (Calcagnotto et al, 2005), whereas others have found no change (Cepeda et al, 2003, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…This allows analysis by standard two-electrode voltage clamp electrophysiology. The advantages and limitations of this technique are discussed in detail elsewhere [13]. Of particular note, absolute current amplitudes measured using this method do not accurately reflect those present in the source tissue; rather, this technique is ideal for determining relative receptor responses to pharmacologic manipulations [19].…”
Section: Resultsmentioning
confidence: 99%
“…Membrane isolation from an additional portion (50–300 mg) of each frozen cortical specimen was performed using the method of [19], with modifications, as detailed in [13]. Xenopus laevis oocyte collection and injection procedures were as described previously [13].…”
Section: Methodsmentioning
confidence: 99%
“…GABA A current rundown has been related to temporal lobe epilepsy [7677] and cortical dysplasia [78]. Functional rundown has also been described in GABA-related transmembrane currents in surgically-resected HH tissue [79].…”
Section: Mechanisms Responsible For Increased Synchronymentioning
confidence: 99%